Human Resource Indicators and Bank Performance - Rahman, Md. Mufidur; Subat, Athkia; Akter, Roksana; Rahman, Mohammad Rifat (STIE Malangkucecwara, 2024)
The study investigates the human resource indicators of selected banks that impact the bank’s profitability performance. By using human resources impact indicators like the number of employees of a bank, the number of branches, deposit collection by per employee, operating profit earned by per employee, and salaries and allowances are given to per employee have impact on banks popular profitability indicator named return on assets. The study is employed on 20 private commercial banks of Bangladesh from according to the data available in between 2014 to 2018. The study's findin gs show that the number of employees of a bank, deposit collection by per employee, operating profit earned by per employee, and salaries and allowances given per employee are significantly impact the bank’s profitability. However, the number of branches of a bank remains insignificant. The study noticed a significant contribution to existing literature related to the human resource context in the banking industry of Bangladesh specially quantifying the contribution of human resources in the profitability of banks. The research suggests policymakers to focus on branch banking to efficiently utilize human resources so that they impact the bank’s profitability and sustainability